Aflati raspunsul
Dau coroană
Anexe:
![](https://ro-static.z-dn.net/files/d40/ffa417dc5a2e70143dd593791f3e0de1.jpg)
Răspunsuri la întrebare
Răspuns de
1
3x(x²-2x)+(x²-1)(x+6)=
3x³-6x²+x³+6x²-x-6=
(3x³+x³)+(-6x²+6x²)-x-6=
4x³-x-6
3x³-6x²+x³+6x²-x-6=
(3x³+x³)+(-6x²+6x²)-x-6=
4x³-x-6
marina3469:
Mulțumesc
Alte întrebări interesante
Engleza,
8 ani în urmă
Matematică,
8 ani în urmă
Fizică,
8 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Latina,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă